O processo criativo de Eugênio Barba: condutas ritualizadas de comunicação na obra O Sonho de Andersen do Odin Teatret - Poty, Vanja (2010)
Based on the critic of the creative processes, the way it is developed by Cecilia Salles (1998 and 2006), this project aims to reflect the ways of Odin Teatret creative organization and its director Eugenio Barba. This discussion is based on the research of the body treatment in the training of its actors, the technique notion and Theatre Anthropology proposal by the group, and a review of its forty-six years of history on the staging of Andersen's Dream, held in 2004. The methodology consisted of literature review, rehearsal analysis, public work demonstrations, performances and interviews. We also approached the communication aspects, physical and symbolic procedures in the construction of the scene, with their restrictions and trends. We will stand out the unfinished, the flow, throw nonlinearity and the mobility of this object, through the debate about the collective dimension of the poetic project and about the part of the director as creator and private spectator of the so called collaborative process. The means of mass communication monopolize the life of society, and exactly because of this we see the scene as a dialogic and nonlinear form of active communication between artists and audience "awakening" the imaginative capacity. From this proposition, we intended to also address the dream and the rite as powers for promoting creation and to question how these work in the scenic construction of the ensemble. As theoretical bases fundamental for such intent, we used investigations of the material imagination concept proposed by Gaston Bachelard (1988, 1990, 1991, 1993 and 1998); analysis of Adriana Mariz (2007) of the construction procedures of the Odin Teatret; studies of Eleazar Meletínski (2002) about the myth and literary archetypes through his approach of the analytical psychology of Carl G. Jung; laboratories theaters of Jerzy Grotowski, Constantin Stanislavsky and Vsevolod Meierhold; the ritual scene of Antonin Artaud; and finally, the archaic practices of self-care reflected in research by Michel Foucault (2006)